2020
DOI: 10.3390/ijerph17103597
|View full text |Cite
|
Sign up to set email alerts
|

Vision Development Differences between Slow and Fast Motor Development in Typical Developing Toddlers: A Cross-Sectional Study

Abstract: Many studies have established a relationship between visual function and motor development in toddlers. This is the first report to study two-year-olds via an assessment of their visual and motor skills. The purpose of this study is to describe the possible changes that can occur between visual and motor systems in typical developing toddlers. A total of 116 toddlers were included in this observational, descriptive, and cross-sectional study. Their mean age was 29.57 ± 3.45 months. Motor development variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…Children with typical development follow a pattern of developing gross and fine motor skills that allows them to know when they are developing well. The development of gross motor skills includes the assessment of muscle control, coordination, and locomotion, while the development of fine motor skills includes the control and coordination of body segments to achieve more complex movement and perceptual skills [ 1 ]. Delayed gross and fine motor development is usually noticed when the child fails to meet the normative development milestones by the normative age [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children with typical development follow a pattern of developing gross and fine motor skills that allows them to know when they are developing well. The development of gross motor skills includes the assessment of muscle control, coordination, and locomotion, while the development of fine motor skills includes the control and coordination of body segments to achieve more complex movement and perceptual skills [ 1 ]. Delayed gross and fine motor development is usually noticed when the child fails to meet the normative development milestones by the normative age [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this classification, we found that all case-control studies (Engel-Yeger 2008;Webber et al 2008;Suttle et al 2011;Niechwiej-Szwedo et al 2017;Kelly et al 2020) were of moderate-high quality and that the single controlled intervention study (Webber et al 2016) was of moderate quality. Regarding the cohort and crosssectional studies, we found seven studies (Wilson & Welch 2013;Alramis et al 2016;Fang et al 2017;Zipori et al 2018;Birch et al 2020;S a et al 2021;Vagge et al 2021) with high quality, and the remaining 10 (Atkinson et al 2005;O'Connor et al 2010;Thompson et al 2017;Birch et al 2019aBirch et al , 2019bHemptinne et al 2020;Niechwiej-Szwedo et al 2020a, 2020bPinero-Pinto et al 2020) (Atkinson et al 2005;Wilson & Welch 2013;Thompson et al 2017;Hemptinne et al 2020;Niechwiej-Szwedo et al 2020a, 2020b from level 3 and five articles (Engel-Yeger 2008;Webber et al 2008;Suttle et al 2011;Niechwiej-Szwedo et al 2017;Kelly et al 2020) from level 4.…”
Section: Quality Of Articles Levels Of Evidence and Data Extractionmentioning
confidence: 76%
“…The systematic review suggests that there is a relationship between the visual system and motor development. Among all the reviewed articles, 9 articles established a relationship between amblyopia and fine and gross motor skills (Engel-Yeger 2008;Webber et al 2008;Suttle et al 2011;Wilson & Welch 2013;Birch et al 2019aBirch et al , 2019bBirch et al 2020;Kelly et al 2020;S a et al 2021), 10 articles associated binocular vision and motor development (O'Connor et al 2010;Alramis et al 2016;Chakraborty et al 2017;Niechwiej-Szwedo et al 2017;Thompson et al 2017;Zipori et al 2018;Hemptinne et al 2020;Niechwiej-Szwedo et al 2020a, 2020bPinero-Pinto et al 2020;Vagge et al 2021), 1 article associated the presence of hyperopia and the impairment of manual dexterity and balance (Atkinson et al 2005), 1 article described how visual perception and motor coordination change in preschool children (Fang et al 2017), and 1 article studied the state of binocular vision and the accommodative system in children with typical motor development (Niechwiej-Szwedo et al 2020a, 2020b.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The occipital lobe is associated with the processing and interpretation of visual information [ 43 ]. Fine motor movement tasks, such as the task performed by participants in the public dataset used, utilize vision for motor planning and spatial perception [ 44 ]. As such, the high performance of the occipital lobe sensors lines up with the known functions of the brain regions.…”
Section: Discussionmentioning
confidence: 99%